Perbandingan Kadar Ureum Sebelum dan Sesudah Hemodialisis Pada Penderita Gagal Ginjal Kronik - Imam Sudarso; Retno Sulistiyowati; Minto Rahaju; Tantri Analisawati Sudarsono (Poltekkes Kemenkes Semarang, 2023)
One of the body's organs, the kidney serves a vital purpose in the excretory and secretory systems. Excretion is the removal of waste products from the body's metabolism, and secretion is the release of chemicals and hormones that are involved in the metabolism of the body. Kidney failure is a condition brought on by kidney damage and is further broken down into acute and chronic forms. Long-lasting kidney damage carries a higher risk to one's health. Hemodialysis is a type of dialysis that helps the kidneys perform their normal functions by removing waste and toxic substances that build up in the blood. This study is analytical observational with a cross-sectional design and a sample of patients with chronic kidney failure at RSUD (Regional Public Hospital) dr. R. Goeteng Taroenadibrata Purbalingga. Non-probability sampling with a purposive sampling method was the sampling technique used. This study compared the urea levels in patients with chronic kidney failure before and after hemodialysis. According to the results of the study, there is a significant difference between urea levels before and after hemodialysis, which had a p-value of 0.003 (sig 0.05).